Assessing the Potential of Valproic Acid as an Adjuvant Agent among Various Histological Subtypes of Thyroid Cancer: A Systematic Review - Makbul, Firshan; Ahani, Ardhi Rahman (http://dharmais.co.id/, 2024)
Background: Valproic acid (VPA) has gained attention as an anticonvulsant drug with potential anti-cancer effects, including in thyroid cancer. It hampers the viability of cancer cells by blocking their cell cycle progression, specifically in the G1 or sub-G1 phases. However, the clinical role of VPA as an adjuvant agent, in addition to the thyroid cancer primary treatment, remains an area of investigation.Methods: We conducted a comprehensive systematic literature review from the first publication available to July 2021. We comprised clinical trials and preclinical investigations that explored VPA’s underlying mechanisms and treatment strategies in thyroid cancer.Results: Fifteen eligible studies were included. Thirteen preclinical studies revealed that VPA significantly enhances therapeutic responses across various histological subtypes of thyroid cancer cells. Regarding clinical implications, recent clinical studies indicated no significant effect on tumor response or overall survival.Conclusions: Our findings highlight the key role of VPA as an alternative therapeutic strategy for thyroid cancer, considering its favorable impact on various histological subtypes. Further welldesigned studies in clinical settings are required to identify the knowledge gap regarding its use in other multimodal treatments such as chemotherapy, surgery, and radiotherapy.